2021
DOI: 10.18203/2394-6040.ijcmph20210788
|View full text |Cite
|
Sign up to set email alerts
|

Survey on common trends for non-prescribed medication use among the young generation in Dhaka, Bangladesh: A cross sectional study

Abstract: Background: Use of drugs without prescription is a worldwide phenomenon especially among the general people in the developing countries. Alarmingly the use of medication without prescriptions among the young generations for longer duration is increasing day by day. The study was meant to evaluate the prevalence of non-prescribed medications among the young generations living in the capital of Bangladesh.Methods: It was a cross-sectional survey conducted in the Dhaka South City Corporation (DSCC) from September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The third part ( Code: PR-3 ) includes questions about the drugs used for self-medication, with 10 different medicine groups most frequently used worldwide 57 , 58 (Supplementary Table 4 ). The researcher incorporated a 5-point Likert scale to measure the practice of consuming those medicines without a prescription.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third part ( Code: PR-3 ) includes questions about the drugs used for self-medication, with 10 different medicine groups most frequently used worldwide 57 , 58 (Supplementary Table 4 ). The researcher incorporated a 5-point Likert scale to measure the practice of consuming those medicines without a prescription.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, knowledge about the eight most commonly consumed medicine groups 57 , 58 was assessed using a five-point Likert scale score ranging from 10 to 40. The reliability among these eight items was within the recommended level (Cronbach’s α = 0.891) along with CFA displayed an overall good fit (CMIN/df = 5.535, RMSEA = 0.052, CFI = 0.982, TLI = 0.954).…”
Section: Methodsmentioning
confidence: 99%
“…29 30 An investigation in Dhaka revealed that 75% of the people polled used over-the-counter drugs, of which 16.90% were antibiotics. 31 It is necessary to address the situation in low-income nations, including Bangladesh, to enhance the overall health impact, given that majority of the world's population resides in these countries. 32 Bangladesh is a densely populated country where 1.8% of the total population comprises indigenous people living in the rural areas of Chittagong, Mymensingh, Sylhet and Rajshahi.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…SMA was shown to be relatively frequent among the people who lived in rural parts of Dhaka, Chittagong and Rajshahi, according to cross-sectional studies that were conducted among participants who lived in those locations 29 30. An investigation in Dhaka revealed that 75% of the people polled used over-the-counter drugs, of which 16.90% were antibiotics 31. It is necessary to address the situation in low-income nations, including Bangladesh, to enhance the overall health impact, given that majority of the world’s population resides in these countries 32…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation